Peranan Pejabat Pembuat Akta Tanah Dalam Pemungutan Bea Peralihan Hak Atas Tanah Dan Bangunan - Jemi Grahono Suryo Gupito (Lex Renaissance, 2020)
This study aims to, first, analyze the role of Land Deed Making Officials (PPAT) in optimizing the collection of Transfer of Land and Building Rights  (BPHTB) in order to achieve legal certainty in Sleman Regency. Second, identifying the obstacles for PPAT in optimizing BPHTB collection in order to realize legal certainty in Sleman Regency. This is a juridical empirical research, with a statutory approach. The results of the study conclude, first, as the vanguard of PPAT in optimizing BPHTB payments in Sleman Regency, namely providing accurate information to taxpayers about the basis for the imposition of BPHTB in accordance with the Sleman Regency Regional Regulation and appealing to prospective taxpayers to provide real information data on the amount of the sale and purchase price of land as the basis for the calculation of BPHTB tax. This is the key to creating legal certainty for the Sleman Regency government itself and taxpayers, the realization of this condition will lead optimiation of BPHTB collection in Sleman Regency. Second, obstacles come from taxpayers from taxpayer ignorance, past buying and selling transactions, to dishonesty from taxpayers in BPHTB payments. It is PPAT's duty to explain and escort taxpayers in the BPHB collection process to comply with the Sleman Regency Regional Regulation.